Quantifying economic policy: Unsupervised learning on archival evidence from the United Kingdom, 1983–2021 - POPA, MIRCEA (European journal of political research, 2024)
The evolution of economic policy in Western countries in the post‐1980 era is subject to extensive academic debate, but statistical modelling of its many qualitative aspects can be challenging. I use two sources of textual data from the United Kingdom – policy documents written by executive departments, as well as recently declassified cabinet minutes – together with unsupervised text‐as‐data methods to examine the evolution of economic policy discourse between 1983 and 2021. The findings challenge the hypothesis of an undifferentiated post‐1980 liberal era. Instead, several shifts away from the liberalizing priorities of the 1980s are identified. The first is an increased attention to the public services in the 1990s. The second is a rise of activist approaches focused on state‐supported innovation in the 2010s – a claim which has been widely articulated but has not been rigorously tested so far. These discourse‐based conclusions are validated through an econometric analysis of detailed spending data.